(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of International Financial Reporting Standards (IFRS) convergence on the Indian banking sector. The transition from Indian Generally Accepted Accounting Principles (GAAP) to IFRS represents a significant shift in accounting practices, aiming to enhance financial transparency and comparability globally. This research explores the implications of IFRS adoption on financial reporting quality, regulatory compliance, and the overall financial performance of Indian banks. By analysing financial statements, regulatory reports, and conducting interviews with industry experts, the study assesses how IFRS convergence has influenced the accuracy and reliability of financial information disclosed by banks. Additionally, the research evaluates the challenges faced by banks during the transition, including the need for system upgrades and staff training, and examines the strategic adjustments made to align with IFRS requirements. The findings offer insights into the benefits and limitations of IFRS convergence for the Indian banking sector, providing valuable information for policymakers, regulators, and financial institutions.